From Junior to Comprehensive Community Colleges in Kansas - Floyd H. Price (Educational Considerations, 1975)
Kansas community colleges have evolved in a short period of years from junior colleges with very limited functions to colleges that are committed to meet the educational and training needs of their communities. The new goals are being accomplished by providing comprehensive programs at a minimal cost to students.